Phenotypic and Functional Changes of Peripheral Ly6C+ T Regulatory Cells Driven by Conventional Effector T Cells - Lee, Jun Young; Kim, Juhee; Yi, Jaeu; Kim, Daeun; Kim, Hee-Ok; Han, Daehee; Sprent, Jonathan; Lee, You Jeong; Surh, Charles D.; Cho, Jae-Ho (Frontiers in Immunology, 2018)
A relatively high affinity/avidity of T cell receptor (TCR) recognition for self-peptide bound to major histocompatibility complex II (self-pMHC) ligands is a distinctive feature of CD4 T regulatory (Treg) cells, including their development in the thymus and maintenance of their suppressive functions in the periphery. Despite such high self-reactivity, however, all thymic-derived peripheral Treg populations are neither homogenous in their phenotype nor uniformly immune-suppressive in their function under steady state condition. We show here that based on the previously defined heterogeneity in the phenotype of peripheral Treg populations, Ly6C expression on Treg marks a lower degree of activation, proliferation, and differentiation status as well as functional incompetence. We also demonstrate that Ly6C expression on Treg in a steady state is either up- or down-regulated depending on relative amounts of tonic TCR signals derived from its contacts with self-ligands. Interestingly, peripheral appearance and maintenance of these Ly6C-expressing Treg cells largely differed in an age-dependent manner, with their proportion being continuously increased from perinatal to young adult period but then being gradually declined with age. The reduction of Ly6C+ Treg in the aged mice was not due to their augmented cell death but rather resulted from down-regulation of Ly6C expression. The Ly6C downregulation was accompanied by proliferation of Ly6C+ Treg cells and subsequent change into Ly6C effector Treg with concomitant restoration of immune-suppressive activity. Importantly, we found that this phenotypic and functional change of Ly6C+ Treg is largely driven by conventional effector T cell population. Collectively, these findings suggest a potential cross-talk between peripheral Treg subsets and effector T cells and provides better understanding for Treg homeostasis and function on maintaining self-tolerance.